RARE-29. Transcriptome characterization of pediatric adamantinomatous craniopharyngioma at the cellular level. (3rd June 2022) - Prince, Eric; Trudeau, Tammy; Chatain, Oscar; Staulcup, Susan; Martinez-Barbera, Juan Pedro; Goerg, Carsten; Hankinson, Todd
Abstract: BACKGROUND: Adamantinomatous Craniopharyngioma (ACP) is a neurologically devastating brain tumor that affects children and adults. It is histologically heterogeneous with epithelial populations that are characterized by the nuclear accumulation of mutated β-catenin, and activated Wnt signaling. Current models suggest that ACP growth is driven through paracine mechanisms characterized by the senescence-associated secretory phenotype (SASP). However, detailed pathogenic mechanisms remain unknown. Improved definition of the various cellular phenotypes that compose ACP will inform and advance our understanding of this disease. METHODS: Single cell RNA-sequencing (scRNA-seq) and multiplex ELISA were performed on pediatric ACP tissue and cyst fluid, respectively. Reference scRNA-seq data was obtained from PanglaoDB. Preprocessing and standard analyses were conducted using Seurat software. Cellular phenotypes were annotated using the Human Primary Cell atlas. Differential expression and functional enrichment analyses were utilized to identify Wnt-signaling activation and epithelial subpopulations. Paracrine signaling was inferred via CellChatDB. SASP Atlas was utilized to query marker gene lists. Pseudotemporal ordering was performed using monocle3. RESULTS: ACP tissue is heterogenous and contains multiple distinct immune signatures. ACP tissue contains 2 unique epithelial subpopulations, which demonstrate canonical Wnt-signaling and SASP, respectively. Pseudotemporal ordering suggests the initial oncogenic event to be of epidermal character, with subsequent aggressive behavior from a separate epithelial cell population. CONCLUSIONS: Based on gene expression, cell populations that correspond to the histologically identifiable epithelial whorls and palisading epithelium can be identified. These subpopulations display unique functional signatures. Simultaneous and synergistic therapeutic targeting of these separate epithelial populations may lead to improved patient care.